Ionic mechanisms underlying bistability in spinal motoneurons: insights from a computational model - Molkov, Yaroslav I.; Krust, Florent; Jeter, Russell; Stell, Tommy; Mohammed, Mohammed A. Y.; Brocard, Frédéric; Rybak, Ilya A. (Frontiers in Cellular Neuroscience, 2025)
Spinal motoneurons are the final output of spinal circuits that engage skeletal muscles to generate motor behaviors. Many motoneurons exhibit bistable behavior, alternating between a quiescent resting state and a self-sustained firing mode, classically attributed to plateau potentials driven by persistent inward currents. This intrinsic property is important for normal movement control, but can become dysregulated, causing motor function deficits, like spasticity. Here we use a conductance-based single-compartment model, together with mouse spinal slice recordings, to investigate the ionic interactions underlying motoneuron bistability. We show that synergistic interactions among high-voltage-activated L-type Ca2+ current (ICaL), calcium-induced calcium release (CICR) and the Ca2+-activated non-specific cation current (ICAN) constitute a minimal mechanistic core that produces plateau potentials and bistable firing. Within this framework, the persistent sodium current (INaP) promotes plateau generation, in contrast to the Ca2+-dependent K+ current (IKCa) which opposes it. These results delineate ionic dependencies at the level of interactions rather than spatial localization and provide a tractable basis for interpreting altered motoneuron excitability in disease.